Gender Representation in an English Textbook Entitled Bahasa Inggris: When English Comes in Handy for Tenth Grade Students - Pebri Prandika Putra; Silfira Yuni Angelia (Linguists : Journal Of Linguistics and Language Teaching, 2021)
Based on categories of Gender visibility and Gender roles theory, gender representation and gender roles have been classified in several Main Characters, Named as Non-active Characters, Non-named, Non-active Characters, Appearances in Illustration, Noun and Pronoun. Therefore,  this research was aimed to find out Gender representation and gender roles in the English textbook entitled Bahasa Inggris When English Comes in Handy for Tenth Grade Students Published by Grafindo Media Pratama. The method of this research is a qualitative study using content analysis. The results of this research show that Male was dominant in categories such as the number of named- non active, non-named-non active, appearance in illustrations and titled & named. Furthermore, female characters were dominant in main characters. Also, the gender roles including domestic gender roles and public gender roles were dominant done by Male. In conclusion, in accordance with Stockdale's theory, the differences between Male and Female gender are more than 5%, then the book can be said to contain gender bias.